ANALISIS PENGARUH CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN - Ramadhan Sukma Perdana; Rahardja Rahardja (Diponegoro Journal of Accounting, 2014)
Financial crisis in many countries as a result of weak good corporate governance practices, have focused attention on the importance of good corporate governance. Application of corporate governance by companies with the objective of creating management good management and accountability for the company's credibility that is expected to enhance firm value. This study aimed to analyze the effect of the application of mechanism corporate governance on firm value. The population of this study is banking companies listed in Indonesian Stock Exchange (IDX) in 2010-2012. The total study observations was 78. Results of this study showed that institutional ownership no significant effect to firm value. Second, audit committee no significant effect to firm value. Third, external auditor no significant effect to firm value. Meanwhile, there are significant effect on managerial ownership and the proportion of independent board to firm value.